Practical Pelvic Floor Ultrasonography : A Multicompartmental Approach to 2D/3D/4D Ultrasonography of the Pelvic Floor - Shobeiri, S. Abbas (Springer International Publishing : Imprint: Springer, 2017)
This new edition provides the most up to date, state-of-the art review of current literature which provides an introduction to pelvic floor imaging, as well as a resource to be used during initial and more advanced practice. The book features new chapters on Vaginal mesh imaging, ultrasound of implanted material, pelvic floor trauma, and ultrasound in pelvic floor therapy. The reader will gain competence in performing transperineal, endovaginal and endoanal 3D/4D ultrasound evaluation of the pelvic floor including anal sphincter and levator ani complex. The text provides a basic understanding of how to perform a transperineal, an endovaginal and endoanal pelvic floor ultrasound and use the desktop 3D/4D softwares to obtain basic measurements. Concise textual information from acknowledged experts is complemented by high-quality diagrams and images to provide a thorough update of this rapidly evolving field. Introductory chapters fully elucidate the anatomical basis underlying disorders of the pelvic floor, followed by 1) 3D/4D transperineal imaging, 2) 3D endovaginal imaging of the urethra and the bladder, Levator ani muscles, the anorectal area, and 3) 3D endoanal imaging. Measurement protocols and case reviews are demonstrated at the conclusion. Written entirely by experts in their fields, the second edition of Practical Pelvic Floor Ultrasonography: A Multicompartmental Approach to 2D/3D/4D Ultrasonography of the Pelvic Floor is a comprehensive resource that will be of great value to urogynecologists, colorectal surgeons, obstetrician and gynecologists, female urologists, ultrasonographers, radiologists, physiotherapists, as well as fellows in urogynecology and colorectal surgery.
Keywords: Medicine.; Gynecology.; Radiology.; Rectum -- Surgery.; Urology.; elektronické knihy; electronic books